Perspektif Lokal dalam Tata Kelola Penanganan Banjir dan Rob di Kota Pekalongan - Shinta Permana Putri; Lintang Rahmayana (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
This study highlights the urgency of addressing the increasingly complex issues of flooding and tidal inundation (rob) in Pekalongan City, where existing mitigation efforts have not yet yielded optimal results. The aim of this research is to identify the problems in flood and tidal inundation management from the community’s perspective, particularly in the aspects of infrastructure, human resources, institutions, and systems. This study employs a qualitative research design. Data were collected through in-depth interviews conducted with key community actors across eleven urban villages affected by flooding and tidal inundation in Pekalongan City. Data analysis was carried out using content analysis techniques, including stages of data reduction, categorization, and interpretation of meanings based on similarities in empirical findings. The results indicate that four main aspects contribute to the suboptimal flood and tidal inundation management efforts in Pekalongan City, namely infrastructure, human resources, institutions, and systems. The infrastructure aspect highlights issues related to the suboptimal function, equity, and maintenance of flood and tidal control facilities. The human resource aspect emphasizes problems of low awareness, participation, and community capacity in mitigation efforts. The institutional aspect points to weak coordination among stakeholders, as well as a lack of transparency and public participation. The system aspect reveals problems with early warning and aid distribution mechanisms that remain unintegrated and ineffective. The findings imply the need for a reformulation of sustainable strategies for flood and tidal inundation management through improving the quality and equity of infrastructure, enhancing community adaptive capacity, strengthening cross-sectoral and interregional coordination, integrating spatial data-based early warning systems, and controlling spatial utilization based on adaptive and mitigation-oriented spatial planning principles.